An Overview of the Implementation of Sbar Communication Techniques in the Inpatient Room of Santa Elisabeth Hospital Medan Year 2024 - Rotua Elvina Pakpahan; Helinida Saragih; Elselina Saragih; Elsat Duha (Jurnal EduHealth, 2025)
SBAR communication is a method used by medical personnel to convey information about the patient's condition. This technique is applied during the nursing handover process, also known as Hand Over, as well as when the patient is transferred to the inpatient room. the type of research in this study is descriptive with a quantitative research design, with a population of 67 respondents, the sampling technique in this study is purposive sampling. The instrument used is the SBAR technique communication observation sheet . Based on the results of direct research to respondents regarding SBAR technique communication (Situation, Background, Assessment, Recommendation), the overall results were good (100%). Based on the results of the study of the description of the application of SBAR communication techniques in the Inpatient Room of Santa Elisabeth Hospital Medan in 2024 with a total of 67 nurses, it was obtained Based on the SBAR communication technique of Nurses in the Inpatient Room of Santa Elisabeth Hospital Medan in 2024 with a good category of 67 respondents (100%).